2018
DOI: 10.1111/jvim.15299
|View full text |Cite
|
Sign up to set email alerts
|

An E321G MYH1 mutation is strongly associated with nonexertional rhabdomyolysis in Quarter Horses

Abstract: BackgroundAn E321G mutation in MYH1 was recently identified in Quarter Horses (QH) with immune‐mediated myositis (IMM) defined by a phenotype of gross muscle atrophy and myofiber lymphocytic infiltrates.Hypothesis/ObjectivesWe hypothesized that the MYH1 mutation also was associated with a phenotype of nonexertional rhabdomyolysis. The objective of this study was to determine the prevalence of the MYH1 mutation in QH with exertional (ER) and nonexertional (nonER) rhabdomyolysis.AnimalsQuarter Horses: 72 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 22 publications
3
42
1
1
Order By: Relevance
“…A missense E321G MYH1 mutation in the gene that encodes the MYH1 protein found in type IIX myofibers was found to be responsible for IMM as well as for a codominantly inherited form of severe acute non‐ER in QH‐related breeds . These 2 myopathies have been grouped under the heading of myosin heavy chain 1 myopathies (MYHM) based on this newly recognized etiology . The major finding in the present study was the relatively common occurrence of the E321G MYH1 mutation in QHs.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A missense E321G MYH1 mutation in the gene that encodes the MYH1 protein found in type IIX myofibers was found to be responsible for IMM as well as for a codominantly inherited form of severe acute non‐ER in QH‐related breeds . These 2 myopathies have been grouped under the heading of myosin heavy chain 1 myopathies (MYHM) based on this newly recognized etiology . The major finding in the present study was the relatively common occurrence of the E321G MYH1 mutation in QHs.…”
Section: Discussionmentioning
confidence: 61%
“…Immune‐mediated myositis in American QHs is characterized by autoimmunity directed at type IIX myofibers, resulting in episodes of marked muscle atrophy . A missense E321G MYH1 mutation in the gene that encodes the MYH1 protein found in type IIX myofibers was found to be responsible for IMM as well as for a codominantly inherited form of severe acute non‐ER in QH‐related breeds . These 2 myopathies have been grouped under the heading of myosin heavy chain 1 myopathies (MYHM) based on this newly recognized etiology .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nonsense mutation in B3GALNT2 involved in muscular dystrophy with hydrocephalus in stillborn foals was discovered previously by the same group using similar techniques (Ducro et al 2015). This approach was also utilized to unravel the genetic mutation responsible for both immune-mediated myositis (Finno et al 2018) and non-exertional rhabdomyolysis (Valberg et al 2018) in the Quarter Horse as well as congenital hepatic fibrosis in the Swiss Franches-Montagnes (Drogemuller et al 2014).…”
Section: Genomics Tools and Resourcesmentioning
confidence: 99%
“…9 Further, Alsaif et al have reported a single case of rhabdomyolysis associated with a homozygous missense variant in MYH1, the gene encoding myosin heavy chain 2X 10 , and a MYH1 missense variant is strongly associated with non-exertional rhabdomyolysis in Quarter horses. 11 In addition, variants in known muscular dystrophy genes can also predispose a patient to rhabdomyolysis; in some cases rhabdomyolysis can be the presenting symptom of an underlying muscular dystrophy, e.g. ANO5, CAV3 DMD, FKRP and SGCA 5; 6; 12-15 or neurogenerative disease, e.g.…”
Section: Introductionmentioning
confidence: 99%